Principal Leadership as a Strategy for Developing Educators and Educational personnel: A Thematic Synthesis of Articles Indexed in SINTA 1 and SINTA 2 - Kasmir Kasmir; Muh. Ardiansyah; Ansar Ansar (FKIP - Universitas Riau, 2026)
Improving the quality of educators and educational personnel is essential for achieving sustainable educational quality. Principals play a strategic role in strengthening school culture, improving teacher and professionalism, and developing the capacity of educational personnel. However, previous studies have mainly examined leadership dimensions separately, resulting in limited comprehensive understanding of principal leadership in educational personnel development. This study aimed to formulate an integrative principal leadership model through a thematic synthesis of SINTA 1 and SINTA 2 indexed articles. A Systematic Literature Review (SLR) following the PRISMA framework was conducted. The search identified 37 articles, of which five met the inclusion criteria after screening and eligibility assessment. Data were analyzed using thematic synthesis. The findings revealed four leadership dimensions contributing to educational personnel development: leadership authority, managerial competence, transformational leadership, and digital leadership. These dimensions interact to strengthen positive school culture, support educational personnel development, and contribute to sustainable educational quality improvement. The study offers a novel integrative leadership framework by combining multiple leadership dimensions and positioning positive school culture as a mediating mechanism linking leadership practices to educational personnel development.